Barrett's Esophagus: A Review of Biology and Therapeutic Approaches - Kountourakis, Panteleimon (International Society of Gastrointestinal Oncology, 2012)
Despite advances in diagnosis and therapy, esophageal cancer remains a highly lethal disease. The incidence of esophageal adenocarcinoma (EAC) has risen faster than that of any other cancer in the western world, and Barrett's esophagus (BE) may be a significant contributing factor. In-depth knowledge of biology of cancer progression and cancer could lead to the identification of biomarkers that are the hallmark of BE's progression. By integrating validated biomarkers of progression into clinical practice, there is a possibility of identifying high-risk patient population for targeted surveillance, and such biomarkers may serve as novel therapeutic targets for chemoprevention and therapy. Clinical management of BE has improved considerably due to the improvements in endoscopic resection and ablation techniques. We discuss the current status of biology and therapeutic approaches to BE.